The Impact of Gamified Learning on Students' Motivation in the EFL Context: Case Study at LKP Uswahedu Global Linguists - Achmad Zainudin (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2024)
Abstract This study investigated the impact of gamified learning on students’ motivation and English language ability in an EFL context at LKP Uswahedu Global Linguists. A pre-experimental one-group pretest–posttest design was employed involving 20 students. Gamified learning activities were implemented before formal learning sessions to create a fun and engaging learning atmosphere and to promote social interaction among students. Students’ motivation was measured using a questionnaire administered before and after the treatment, while their English language ability was assessed through pretest and posttest measures. The data were analyzed using descriptive statistics and a paired-samples t-test. The findings revealed a statistically significant increase in students’ motivation after the implementation of gamified learning, as indicated by an increase in the mean score from 64.75 to 78.35 (p < .05). However, the results showed no highly significant improvement in students’ English language ability. This suggests that although gamified learning effectively enhances students’ motivation and positive attitudes toward learning English, it does not automatically lead to substantial gains in language proficiency. Several factors may explain this finding, including students’ greater focus on game mechanics than on learning content, limited alignment between game design and learning objectives, and insufficient reflection and feedback after gameplay. This study contributes to the existing literature by providing evidence from a non-formal EFL context and by positioning gamified learning as a motivational tool rather than a stand-alone instructional method. The findings imply that teachers need to design more educationally meaningful games that clearly embed learning objectives and provide adequate opportunities for meaningful language practice and feedback. Future research is recommended to employ more rigorous experimental designs and longer interventions to examine the long-term effects of gamification on language development. Keywords: gamified learning; EFL; student motivation; language proficiency; non-formal education